2023
DOI: 10.1007/s00586-023-07604-9
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS PRIZE in Clinical Science 2023: comparison of degenerative MRI features of the intervertebral disc between those with and without chronic low back pain. An exploratory study of two large female populations using automated annotation

Abstract: Objectives The relationship of degeneration to symptoms has been questioned. MRI detects apparently similar disc degeneration and degenerative changes in subjects both with and without back pain. We aimed to overcome these problems by re-annotating MRIs from asymptomatic and symptomatics groups onto the same grading system. Methods We analysed disc degeneration in pre-existing large MRI datasets. Their MRIs were all originally annotated on different scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…З іншого боку, усі без виключення перераховані вище клінічні явища можуть спричинятися не лише ДЗД і не лише якимись його уже описаними на даний час патоморфологічними характеристиками, а й іншою патологією. Приміром, радіологічні кореляти ДЗД виявляють у осіб, котрі не мали за усього життя і не мають на момент дослідження жодних ознак болю у спині чи симптомати-ки радикулопатії [13,37]. З іншого боку, більшість випадків, наприклад, болю у попереку не мають підтверджених доступними на даний час методами патоморфологічних змін у хребті чи прилеглих тканинах [47], тобто відносяться до категорії так званого неспецифічного болю у спині (англ.…”
Section: другий клас включає патоморфологічні/патофізіологічні терміниunclassified
“…З іншого боку, усі без виключення перераховані вище клінічні явища можуть спричинятися не лише ДЗД і не лише якимись його уже описаними на даний час патоморфологічними характеристиками, а й іншою патологією. Приміром, радіологічні кореляти ДЗД виявляють у осіб, котрі не мали за усього життя і не мають на момент дослідження жодних ознак болю у спині чи симптомати-ки радикулопатії [13,37]. З іншого боку, більшість випадків, наприклад, болю у попереку не мають підтверджених доступними на даний час методами патоморфологічних змін у хребті чи прилеглих тканинах [47], тобто відносяться до категорії так званого неспецифічного болю у спині (англ.…”
Section: другий клас включає патоморфологічні/патофізіологічні терміниunclassified
“…Additionally, they failed to incorporate variables such as the degree of intervertebral disc degeneration, calcification of herniated intervertebral discs, and ossification of the posterior longitudinal ligament (OPLL) as imaging characteristics to be included in the study. Nevertheless, literature has documented that disc degeneration correlates with the initiation of patient symptoms [ 17 , 18 ], weakening of spinal ligament integrity [ 19 ], and alterations in interlevel spinal motion [ 20 ]. Certain scholars [ 21 ] have substantiated that OPLL is an independent risk factor influencing the prognosis of respiratory function post-cervical cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…component of the problem, thus favoring the 'psycho-social' aspects such as catastrophizing, fear/anxiety and avoidance behavior components in the development of chronic pain in the patient [1][2][3][4][5][6][7][8][9], as some authors are quite adamant that the 'tissue injury' component plays a rather limited role [6]. It can be argued, though, that the lack of appreciation for the tissue component of spine pain/disorders is shortsighted, based on an incomplete review of recent systematic reviews, and based on limitations with early analytical methods, whereas today's technology and more detailed investigations have identified a significant role for the tissue component as contributing to the presence and development of chronic spine pain and disability [12][13][14][15]. Furthermore, proponents of the stronger role that the 'psycho-social' part of the equation plays in spine conditions often fail to acknowledge that recent systematic literature reviews with meta-analysis have identified a clear controversy regarding the quality and true impact that fear-avoidance, pain-catastrophizing (PC), and 'psycho-social' model elements play in individuals with chronic musculoskeletal pain (CMP) disorders [7][8][9]; for example, the following has been stated: "Despite the very low quality of the available evidence, the general consistency of the findings highlights the potential role that PC may play in delaying recovery from CMP.…”
Section: Introductionmentioning
confidence: 99%